ANALISIS PENGGUNAAN LAHAN DAN ARAHAN PENGENDALIAN PEMANFAATAN RUANG DI KABUPATEN BOGOR - Ely Triwulan Dani; Santun R.P. Sitorus; Khursatul Munibah (TATALOKA, 2017)
Bogor Regency has three strategic functions, as a buffer zone of Jakarta, water system conservation area, and agricultural development area. Rapid population growth led to the need for land better place to live and businesses, it triggers a change in land use that resulted in the violation of spatial pattern plan. Therefore, the spatial usage must be controlled, in order to be in line with the spatial pattern plan and support functions of Bogor Regency. The main purpose of this study was to formulate the control direction of spatial usage in Bogor Regency. The spatial analysis used to obtain information on land use, land ownership, location permits, and evaluation of land use on spatial pattern plan. Schallogram method used to determine the level of the hierarchy of the region, and factors affecting the inconsistency of land use on spatial pattern plan obtained by the analysis of field data. Formulation of the directives controlling spatial utilization is obtained by descriptive analysis. The results showed that 51.33% of exsisting land use in Bogor Regency has not been done and still can be directed in order to conform with the spatial pattern plan, the remaining 38.06% was suitable and unsuitable 10.62%. The factors that cause such inconsistency were the lack socialization policy less, the absence of licensing, housing needs, public facilities availability and accessibility, lands of usage before defined spatial pattern plan, the transfer of land ownership, and sortage of agricultural support facilities. The implications of these results were necessary to apply four control instruments, those are licensing, zoning regulations, provision of incentives and disincentives, and sanctions. Besides, the need for policy dissemination and surveillance, monitoring and evaluation periodically.